Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/uog.14678
|View full text |Cite
|
Sign up to set email alerts
|

How can we measure bladder volumes in women with advanced pelvic organ prolapse?

Abstract: Objectives To compare bladder volumes determined by three different formulae using measurements obtained from two-dimensional translabial ultrasound (2D-US), with true bladder volumes, in women with advanced pelvic organ prolapse (POP). Methods (rho, 0.818-0.849) and concordance (ICC, were found between total measured volume (volume of spontaneous bladder voiding + volume obtained from catheterization) and the volume determined by US using the three different formulae, as well as between the post-void residual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
(17 reference statements)
1
7
0
Order By: Relevance
“…Dicuio’s formula with PC of 0.52 has been shown to underestimate volumes . This was also shown in our study, where 59% of estimated bladder volumes were less than the catheterised volume.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Dicuio’s formula with PC of 0.52 has been shown to underestimate volumes . This was also shown in our study, where 59% of estimated bladder volumes were less than the catheterised volume.…”
Section: Discussionsupporting
confidence: 87%
“…Errors in calculating bladder volume can be as high as 25% . 2D scans may be inaccurate because the bladder can have an irregular shape .…”
Section: Introductionmentioning
confidence: 99%
“…In the past years, many experiences on the application and utility of TL‐US in different fields of obstetrics and gynecology were published, such as intrapartum evaluations, quantification of PVR, and grade of uterine descent 26–29 . Recently, Illiano et al 30 reported results of the dynamic TL‐US evaluation performed at follow‐up after TOT procedure in order to recognize possible associated factors with failed surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In the past years, many experiences on the application and utility of TL-US in different fields of obstetrics and gynecology were published, such as intrapartum evaluations, quantification of PVR, and grade of uterine descent. [26][27][28][29] Recently, Illiano et al 30 compared with continent women had the sling in a proximal or distal position, which moved discordantly with the urethra (p < 0.0001), with asymmetry arm and bladder neck funneling (P < 0.0001). 30…”
Section: Comparisons With Other Studiesmentioning
confidence: 99%
“…For example, post-void residual (PVR) volume is utilized in the diagnosis of urinary retention, detrusor underactivity, and other bladder impairments [ 1-4 ]. In addition, measurements of both voided volume and PVR are needed for bladder training and other bladder assessments [ 5 , 6 ]. During urodynamics (UD), bladder volume during filling is assumed to be equal to the infused volume and does not typically include an estimation of urinary diuresis.…”
Section: Introductionmentioning
confidence: 99%